2017
DOI: 10.18632/oncotarget.20239
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-related biological markers as predictors of epirubicin-based treatment responsiveness and resistance in locally advanced breast cancer

Abstract: PurposeTo identify hypoxia-related biomarkers indicative of response and resistance to epirubicin treatment in patients with locally advanced breast cancer.Patients and MethodsOne hundred seventy-six women with T2-4 N0-1 breast tumours were randomly assigned to receive epirubicin 120 mg/m2/1-21 (EPI ARM), epirubicin 120 mg/m2/1-21 + erythropoietin 10.000 IU sc three times weekly (EPI-EPO ARM) and epirubicin 40 mg/m2/w-q21 (EPI-W ARM). Sixteen tumour proteins involved in cell survival, hypoxia, angiogenesis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
5
0
2
Order By: Relevance
“…CAV1, an integral structural component of caveolae, is a direct target of HIF-1. Numerous studies have recently demonstrated that hypoxia-associated biological markers can be used as predictors of treatment, metastasis and prognosis in various types of cancer, including breast, lung and colorectal cancer (1517). The present study revealed that HIF-1α and CAV1 were significantly upregulated in patients with IDH-wild type GBM.…”
Section: Discussionmentioning
confidence: 99%
“…CAV1, an integral structural component of caveolae, is a direct target of HIF-1. Numerous studies have recently demonstrated that hypoxia-associated biological markers can be used as predictors of treatment, metastasis and prognosis in various types of cancer, including breast, lung and colorectal cancer (1517). The present study revealed that HIF-1α and CAV1 were significantly upregulated in patients with IDH-wild type GBM.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally acknowledged that tumor hypoxia and multiple HIF-related markers predict worse response to chemoradiotherapy, and neoadjuvant studies have shown lower pathologic complete response (pCR) rates in patients with high baseline HIF expression (22,(103)(104)(105).…”
Section: Predictive Markersmentioning
confidence: 99%
“…Recent studies have shown that the contribution of CK2 and PIM-1 kinases to the regulation of transcription, differentiation, or signaling of DNA damage/repair systems is achieved by regulating survival pathways and hypoxia [ 23 ]. The activity of both CK2 and PIM-1 has been demonstrated to be elevated in hypoxia, which increases HIF-1 transcriptional activity (hypoxia-induced factor), whereas under normoxia, this factor is degraded [ 24 ].…”
Section: Introductionmentioning
confidence: 99%